Message - Audu-Peter , Dr. Jennifer Drambi (Universal Journal of Pharmaceutical Research, 2024)
A recurrent topical discussion the world over among world leaders and advocates is “Climate Change”. It is so important that it is the over-riding issue over countries’ industrial planning and development. Advocates are predicting dire consequences in the coming decade and that by 2030; the global temperatures would rise by 1.5oC, to negatively impact on the climate. As a result, there will be increase in intensity and frequencies of fires, storms and periods of drought, affecting biodiversity and causing changes in the ecosystem. Changes in the habitat of animals, microorganisms and plants are envisaged with some getting extinct, consequently, there may be new disease patterns and spread in new communities, with resurgence of unknown diseases or those that have long been eliminated. The challenge to Low and Middle Income Countries (LMIC) is huge, because majority access their therapies from the ecosystem. As many medicinal plants are impacted by climate change with upsurge in spread and intensity of old and new diseases, pharmaceutical product development would be impacted, requiring actions that identify and cultivate vulnerable species, as well as production planning by pharmaceutical industries to produce therapies in anticipation of emergence of old or new diseases, including planning for pandemic diseases. Researchers may begin to tailor their research towards finding solutions to these predicted emergencies.